Asesmen Formatif Pada Pendidikan Anak Usia Dini Di Indonesia - Agung Prihantoro (UIN Sultan Maulana Hasanuddin Banten, 2021)
Formative assessment in early childhood education in Indonesia does not have been working well. The research aims to prove the problem that the formative assessment (assessment for learning and assessment as learning) in early childhood education in Indonesia does not have been performing well. The research employed the research methodology of literature review to investigate the problem by analyzing empirical research-based articles on assessment in early childhood education. The result shows that a very few of natures of the formative assessment were present when teachers of early childhood education assessed their students. Goals, teacher's and student's roles, methods, feedback and following actions which particularly characterize the formative assessment were seldom found in the assessment practice in early childhood education in Indonesia. Keywords: formative assessment; assessment for learning; assessment as learning; early childhood education References Adinda, W.N., Wahyuni, S. & Majidah, K. (2020). Penilaian Autentik pada Pembelajaran Kreativitas Anak Usia Dini di Annur I Sleman Yogyakarta. Raudhah 8 (1). 92-104. http://jurnaltarbiyah.uinsu.ac.id/ index.php/raudhah/article/view/589 Afni, Nurul. (2016). Pelaksanaan Evaluasi Tingkat Pencapaian Perkembangan Anak Usia Dini di TK Se-Kecamatan Payung Sekaki Kota Pekanbaru. Jurnal Educhild: Pendidikan dan Sosial 5 (2). 128-133. https://educhild.ejournal.unri.ac.id/ index.php/JPSBE/article/view/3835/0 Ahsunandar, La O. (2020). Evaluasi Pelaksanaan Standar Produk Hasil Belajar pada Satuan Pendidikan Anak Usia Dini. Al-Ta'dib Jurnal Kajian Ilmu Kependidikan 13 (1). 34-45. https://ejournal.iainkendari.ac.id/ index.php/al-tadib/article/view/1775 Akhsanti, Munika S. (2014). Pemanfaatan Hasil Evaluasi Pembelajaran dalam Pengembangan Program Pembelajaran Anak Usia Dini. Early Childhood Papers (Belia) 3 (2). 87-94. https://journal.unnes.ac.id/sju/ index.php/belia/article/view/3761 Ali, M.M. & Hamid, O. (2020). Teaching English to the Test: Why Does Negative Washback Exist within Secondary Education in Bangladesh? Language Assessment Quarterly 17 (2). 1-18. https:// www.tandfonline.com/doi/abs/10.1080/15434303.2020.1717495?journalCode=hlaq20 Allal, Linda. (2019). Assessment and the co-regulation of learning in the classroom. Assessment in Education: Principles, Policy & Practice 27 (4). 1-18. https://www.tandfonline.com/doi/abs/10.1080/0969594X.2019.1609411? journalCode=caie20 Chen, P.P. & Bonner, S.M. (2019). A framework for classroom assessment, learning, and self-regulation. Assessment in Education: Principles, Policy & Practice 27 (4). 373-393. https://www.tandfonline.com/ doi/abs/10.1080/0969594X.2019.1619515?journalCode=caie20 Chong, Sin W. (2018). Three Paradigms of Classroom Assessment: Implications for Written Feedback Research. Language Assessment Quarterly 15 (4). 330-347. https://www.tandfonline.com/doi/abs/10.1080/15434303.2017.1405423 Damayanti, E., Hartika, A.S., Herawati, Lisna, Jannah, R. & Pratiwi, S.I. (2018). Manajemen Penilaian Pendidikan Anak Usia Dini pada Taman Kanak-Kanak Citra Samata Kabupaten Gowa. Nanaeke Indonesian Journal of Early Childhood Education 1 (1). 13-24. http://journal.uin-alauddin.ac.id/index.php/nanaeke/article/view/135-142 Davies, R. & Hamilton, P. (2016). Assessing learning in the early years' outdoor classroom: examining challenges in practice. Education 3-13 International Journal of Primary, Elementary and Early Years Education 46 (1). 117-129 https://www.tandfonline.com/doi/abs/10.1080/03004279.2016.1194448 DeLuca, C., Pyle, A., Braund, H. & Faith, L. (2020). Leveraging assessment to promote kindergarten learners' independence and self-regulation within play-based classrooms. Assessment in Education: Principles, Policy & Practice 27 (4). 394-415. https://www.tandfonline.com/ doi/full/10.1080/0969594X.2020.1719033 DeLuca, C., Pyle, A., Valiquette, A. & LaPointe-McEwan, D. (2020). New Directions for Kindergarten Education Embedding Assessment in Play-Based Learning. The Elementary School Journal 120 (3). 455-479. https:// www.journals.uchicago.edu/doi/10.1086/707008 Dewi, N.P., Poerwanti, J.I.S. & Sutijan, 2019). Penerapan Penilaian Portofolio dalam Asesmen Perkembangan Motorik Halus Anak di TK Se-Gugus Arjuna Kecamatan Jatipurno. Jurnal Kumara Cendekia 7 (1). 16-25. https:// jurnal.uns.ac.id/kumara/article/view/35628 Earl, L. & Katz, S. (2006). Rethinking Classroom Assessment with Purpose in Mind: Assessment for Learning Assessment as Learning Assessment of Learning. Manitoba: Crown in Right of Manitoba. Goldstein, J. & Flake, J.K. (2015). Towards a framework for the validation of early childhood assessment systems. Educational Assessment, Evaluation and Accountability 28 (3). 273-293. https://link.springer.com/ article/10.1007/s11092-015-9231-8 Hartati, Sofia. (2017). Pengembangan Model Asesmen Perkembangan Anak Taman Kanak-Kanak di DKI Jakarta. Jurnal Pendidikan Usia Dini. 19-30. http://journal.unj.ac.id/unj/index.php/jpud/article/view/2522 Hasanah. F. & Uyun, Q. (2019). Asesmen Perkembangan Kognitif Anak Usia Dini (Studi Kasus TK Khadijah Al-Muayyada Sampang). Islamic EduKids: Jurnal Pendidikan Anak Usia Dini 1 (1). 31-37. https:// journal.uinmataram.ac.id/index.php/IEK/article/view/1814 Hu, B.Y., Li, Y., Zhang, X., Roberts, S.K. & Vitiello, G. (2021). The quality of teacher feedback matters: Examining Chinese teachers' use of feedback strategies in preschool math lessons. Teaching and Teacher Education 98. 1-14. https://www.sciencedirect.com/science/article/abs/pii/S0742051X2031444X Kamar, Eka M. (2018). Pengembangan Perangkat Evaluasi Perkembangan Bahasa Anak Usia Dini pada Anak TK Islam Al Markaz Al Islami Kelompok B Makassar. Pembelajar: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran 2 (2). 92-100. https://ojs.unm.ac.id/ pembelajar/article/view/5642 Lam, Ricky. (2015). Assessment as learning: examining a cycle of teaching, learning, and assessment of writing in the portfolio-based classroom. Studies in Higher Education 41 (11). 1900-1917. https://www.tandfonline.com/doi/abs/10.1080/03075079.2014.999317 Miles, M.B., Huberman, A.M. & Saldana, J. (2014). Qualitative Data Analysis: A Methods Sourcebook. Edition 3. Thousand Oaks: SAGE Publications, Inc. Novianti, R., Puspitasari, E. & Chairilsyah, D. (2013). Pemetaan Kemampuan Guru PAUD dalam Melaksanakan Asesmen Perkembangan Anak Usia Dini di Kota Pekanbaru. Jurnal Sorot 8 (1). 95-104. https:// sorot.ejournal.unri.ac.id/index.php/JS/article/view/2353/0 Nugraha, E. (2016). Evaluasi Pendidikan Pada Jenjang PAUD. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 106-118. Nurhayati, S. & Rakhman, A. (2017). Studi Kompetensi Guru PAUD dalam Melakukan Asesmen Pembelajaran dan Perkembangan Anak Usia Dini di Kota Cimahi. Jurnal Pendidikan Anak 6 (2) 109-120. https:// journal.uny.ac.id/index.php/jpa/article/view/17699 Nurlaili. (2019). Implementasi Penilaian Pembelajaran Anak Usia Dini di RA Khairin Medan Tembung. Raudhah 7 (1). 93-110. http:// jurnaltarbiyah.uinsu.ac.id/index.php/raudhah/article/download/471/417 Prihantoro, Agung. (2021). Tiga Paradigma Evaluasi Pendidikan: Sebuah Peta Perkembangan. Academy of Education Journal 12 (1). 22-38.https://jurnal.ucy.ac.id/index.php/fkip/article/view/430 Purwasih, Wahyu. (2018). Teknik Penilaian Unjuk Kerja dan Catatan Anekdot sebagai Upaya Pemantauan Perkembangan Anak Di Paud Aisyiyah Sukoharjo Jawa Tengah. Jurnal Warna 2 (2), 76-86. https://ejournal.iaiig.ac.id/index.php/warna/article/view/92 Pyle, A. & DeLuca, C. (2013). Assessment in the Kindergarten Classroom: An Empirical Study of Teachers' Assessment Approaches. Early Childhood Education Journal 41 (5). 373-380. https://link.springer.com/ article/10.1007/s10643-012-0573-2 Pyle. A. & DeLuca, C. (2016). Assessment in play-based kindergarten classrooms: An empirical study of teacher perspectives and practices. The Journal of Educational Research 41 (5). 373-380. https://link.springer.com/article/10.1007/s10643-012-0573-2 Snyder, Hannah. (2019). Literature review as a research methodology: An overview and guidelines. Journal of Business Research. Journal of Business Research 104. 333--339. https://www.sciencedirect.com/ science/article/pii/S0148296319304564 Suyadi. (2016). Perencanaan dan Asesmen Perkembangan pada Anak Usia Dini (Studi Kasus pada Lembaga Pendidikan Anak Usia Dini (PAUD/TK/RA) di Daerah Istimewa Yogyakarta.